Long-Term Treatment with the Combination of Rivaroxaban and Aspirin in Patients with Chronic Coronary or Peripheral Artery Disease: Outcomes During the Open Label Extension of the COMPASS trial. Issue 8 (6th April 2022) - Eikelboom, John W; Bosch, Jacqueline; Connolly, Stuart J; Tyrwitt, Jessica; Fox, Keith A A; Muehlhofer, Eva; Neumann, Christoph; Tasto, Christoph; Bangdiwala, Shrikant I; Diaz, Rafael; Alings, Marco; Dagenais, Gilles R; et al.
Abstract: Aims: To describe outcomes of patients with chronic coronary artery disease (CAD) and/or peripheral artery disease (PAD) enrolled in the Cardiovascular Outcomes for People Using Anticoagulation Strategies (COMPASS) randomized trial who were treated with the combination of rivaroxaban 2.5 mg twice daily and aspirin 100 mg once daily during long-term open-label extension (LTOLE). Methods and results: Of the 27  395 patients enrolled in COMPASS, 12  964 (mean age at baseline 67.2 years) from 455 sites in 32 countries were enrolled in LTOLE and treated with the combination of rivaroxaban and aspirin for a median of 374 additional days (range 1–1191 days). During LTOLE, the incident events per 100 patient years were as follows: for the primary outcome [cardiovascular death, stroke, or myocardial infarction (MI)] 2.35 [95% confidence interval (CI) 2.11–2.61], mortality 1.87 (1.65–2.10), stroke 0.62 (0.50–0.76), and MI 1.02 (0.86–1.19), with CIs that overlapped those seen during the randomized treatment phase with the combination of rivaroxaban and aspirin. The incidence rates for major and minor bleeding were 1.01 (0.86–1.19) and 2.49 (2.24–2.75), compared with 1.67 (1.48–1.87) and 5.11 (95% CI 4.77–5.47), respectively, during the randomized treatment phase with the combination. Conclusion: In patients with chronic CAD and/or PAD, extended combination treatment for a median of 1 year and a maximum of 3 years was associated with incidence rates for efficacy and bleeding that were similar to or lower than those seen during the randomized treatment phase, without any new safety signals.